Depot differences in adipose tissue metabolism and function in obese black South African women and changes in response to an exercise training intervention - Nono Nankam, Pamela Arielle (Department of Human Biology, 2021)
Black South African (SA) women are disproportionally affected by obesity and insulin resistance, which have been associated with depot-specific alterations in adipose tissue function. This thesis aimed to evaluate the differences in fatty acid (FA) composition and gene expression between abdominal (aSAT) and gluteal subcutaneous adipose tissue (gSAT), and the changes in response to exercise training in relation to body composition, hepatic fat, inflammatory and oxidative stress markers, and insulin sensitivity (SI) in obese black SA women. This research evaluated the i) FA composition of aSAT and gSAT, and red blood cell total phospholipids (RBC-TPL) and their associations with body composition, hepatic fat and SI, ii) changes in these FA profiles in response to exercise training and the relationship with changes in systemic inflammation, hepatic fat and SI; iii) effects of exercise training on systemic markers and SAT gene expression of inflammation and oxidative stress; and iv) regional differences in transcriptome profiles of aSAT and gSAT pre- and post-exercise training. Forty-five IsiXhosa women (30-40kg/m2 , 20-35 years) were randomized into control (n=22) or exercise groups (n=23; 12-week aerobic-resistance training, 40-60 min/session, 4 days/week). Pre and postintervention measurements included: anthropometry, body composition, cardiorespiratory fitness, dietary intake, SI, hepatic fat, systemic markers and SAT gene expression of adipokines, inflammation and oxidative stress, RBC-TPL and SAT fatty acids profiles, and untargeted SAT gene expression analyses. The main findings showed differences in the circulating (RBC-TPL) and stored (SAT) FA composition, which reflected in different associations between these FA profiles and SI. Moreover, the changes in FA composition in response to exercise training were depot-specific, with the changes in RBC-TPL correlating with a decrease in systemic inflammation and hepatic fat. Exercise training alleviated systemic oxidative stress and induced increased gSAT inflammatory genes, reflecting SAT remodelling. These changes coincided with a reduction in gynoid fat and were not associated with increased SI. Furthermore, there were unique depot-specific gene expression signatures relating to embryonic development at baseline and more diverse functional-related processes at post-training. This generated novel candidate genes potentially implicated in the relationship between body fat distribution and metabolic status in obese black SA women.